2003
DOI: 10.1023/a:1025485503911
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Using the method of flow cytofluorometry we found that proteinase activity eliminating antigenic determinants from the surface of tumor cells disappeared from the serum of mice with Ehrlich carcinoma. This activity towards Ehrlich carcinoma cells is present in the sera of mice without tumors and in mice with other transplanted tumors. The serum from mice of one strain with Ehrlich carcinoma showed no protease activity against Ehrlich carcinoma cells in mice of other strain. Hence, Ehrlich carcinoma growth is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Metastatic growth of only resected tumor was observed in animals with two transplanted tumors (Ehrlich carcinoma and B16 melanoma); the life span was determined by the growth rate of the more rapidly growing tumor (B16 melanoma), this indicating some specific effect. This specific effect cannot be mediated by the known angiogenic factors [2,3,6], because they should be common for all tumors and stimulate metastatic growth of both Ehrlich carcinoma and B16 melanoma after resection of one of the tumors. We think that the specific inhibitory effect of the primary tumor can be due to peculiar glycosylation and subsequent formation of complexes of serum proteins with the tumor [3][4][5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metastatic growth of only resected tumor was observed in animals with two transplanted tumors (Ehrlich carcinoma and B16 melanoma); the life span was determined by the growth rate of the more rapidly growing tumor (B16 melanoma), this indicating some specific effect. This specific effect cannot be mediated by the known angiogenic factors [2,3,6], because they should be common for all tumors and stimulate metastatic growth of both Ehrlich carcinoma and B16 melanoma after resection of one of the tumors. We think that the specific inhibitory effect of the primary tumor can be due to peculiar glycosylation and subsequent formation of complexes of serum proteins with the tumor [3][4][5].…”
Section: Resultsmentioning
confidence: 99%
“…This specific effect cannot be mediated by the known angiogenic factors [2,3,6], because they should be common for all tumors and stimulate metastatic growth of both Ehrlich carcinoma and B16 melanoma after resection of one of the tumors. We think that the specific inhibitory effect of the primary tumor can be due to peculiar glycosylation and subsequent formation of complexes of serum proteins with the tumor [3][4][5]. The formation of complexes with serum proteins (the complex consists of 4 proteins, one of which is haptoglobin with 20% carbohydrates) was detected in mice with Ehrlich carcinoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ehrlich carcinoma and CaO-1 ovarian carcinoma cells were transplanted intramuscularly (10 6 cells in 0.2 ml RPMI-1640) [1]. Lymphocytes were isolated from the peripheral blood of mice on day 15 after tumor transplantation by the standard method in 1.093 density gradient [3]. Each experiment was repeated at least 3 times.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, there are virtually no data on tumor-specific changes in the body during tumor growth. The presence of these changes is demonstrated in reports indicating that serum and leukocytes of animals with transplanted tumors are characterized by a specific biological effect protecting tumor cells in the host [4,5,7]. We showed that Ehrlich carcinoma causes changes in mouse serum, specific of this tumor [2].…”
mentioning
confidence: 85%